Contraceptive Characteristics of Women Living with HIV in the Kumasi Metropolis, Ghana - Gyimah, Akosua A.; Nakua, Emmauel K.; Owusu-Dabo, Ellis; Otupiri, Easmon (International Journal of MCH and AIDS, 2023)
This article is published in International Journal of MCH and AIDS (2013), Volume 2, Issue 1, Pages 111-120